Respuesta :

Answer:

m = -32.10

Step-by-step explanation:

You solve this the same way you do any two-step linear equation.

1. Subtract the constant that is on the side of the equal sign with the variable term:

m/5 = -6.42

2. Multiply by the inverse of the coefficient of the variable. That means multiply by 5 in this case.

m = 5·(-6.42) = -32.10

_____

Of course, the rules of equality tell you whatever you do to one side of the equation must also be done to the other side. So, when we say subtract 0.12, we mean subtract 0.12 from both sides of the equation. The same for multiplication or division.

Subtract 0.12 from both sides

m/5 = -6.3 - 0.12

Simplify -6.3 - 0.12 to -6.42

m/5 = -6.42

Multiply both sides by 5

m = -6.42 × 5

Simplify 6.42 × 5 to 32.1

m = -32.1

ACCESS MORE